2010
DOI: 10.1182/blood-2010-05-283549
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying γδ T-cell subset perturbations in SIV-infected Asian rhesus macaques

Abstract: Introduction␥␦ T cells are a minor group of T lymphocytes and are distinct from ␣␤ T cells. 1,2 In humans and nonhuman primates, ␥␦ T cells are composed of 2 predominant subsets based on the differential expression of V␦1 and V␦2 genes. Although the antigen specificity and recognition properties of these 2 subsets have yet to be fully elucidated, 3 ␥␦ T cells can expand during bacterial infections. 4 Indeed, V␦1 T cells can recognize small lipoprotein antigens produced by bacterial pathogens, 5 and V␦2 T cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 48 publications
4
54
2
Order By: Relevance
“…Overall, this suggests that the loss of MAIT cells in CVID and other diseases could reflect the infection burden. Microbial translocation is now recognized as a driver of immune activation in HIV infection (49) and is associated with an abnormal distribution of d1 and d2 gd T cells in SIV infection (50). We have recently reported that similar perturbations in gd T cells also occur in CVID (32), and in the current study we observed a trend toward an association between the levels of sCD14, an indirect marker of microbial translocation, and MAIT cell loss in CVID.…”
Section: Discussionsupporting
confidence: 68%
“…Overall, this suggests that the loss of MAIT cells in CVID and other diseases could reflect the infection burden. Microbial translocation is now recognized as a driver of immune activation in HIV infection (49) and is associated with an abnormal distribution of d1 and d2 gd T cells in SIV infection (50). We have recently reported that similar perturbations in gd T cells also occur in CVID (32), and in the current study we observed a trend toward an association between the levels of sCD14, an indirect marker of microbial translocation, and MAIT cell loss in CVID.…”
Section: Discussionsupporting
confidence: 68%
“…Importantly, while γδT cells make up a small percentage of peripheral blood T cells, they are present at high frequencies in the gut [110], where they could potentially play a major role in protection against HIV/SIV. Here we will limit our discussion to their antibody interactions, which represent a small fraction of their overall impact on the immune system.…”
Section: Effector Cellsmentioning
confidence: 99%
“…In contrast, Vγ9Vδ2 T cells, the Vδ2 subset, are mainly found in peripheral blood and are activated by non-peptidic molecules, such as phosphoantigens, produced by many microbial pathogens and stressed cells (5, 6). Activated γδ T cells exhibit a multiplicity of effector functions including direct killing of infected cells, antibody dependent cellular cytotoxicity (ADCC), and production of cytokines such as IFN-γ (7) and IL17 (8, 9). γδ T cells have antigen presenting and regulatory functions and through cross-talk enhance the cytotoxic effector function of NK cells (10).…”
Section: Introductionmentioning
confidence: 99%